Zooplankton functional traits in a tropical estuarine system: Are lower and upper estuaries functionally different? - Sanvicente-Añorve, Laura; Sánchez-Campos, Mitzi; Alatorre-Mendieta, Miguel; Lemus-Santana, Elia; Guerra-Castro, Edlin (Frontiers in Marine Science, 2022)
Functional diversity measures help to understand the underlying mechanisms explaining the relationship between organisms and environment. This work examined the mesozooplankton community of an estuary under the hypothesis that the upper (< 25 psu) and lower (> 25 psu) zones are functionally different in terms of feeding strategies, trophic groups, camouflage, buoyancy, and defense against predators, due to the salinity gradient. We used the ‘community-weighted mean trait values’ (CWM) in combination with three functional indices (FRic: functional richness, FEve: functional evenness, FDiv: functional divergence) to test our hypothesis. Zooplankton samples were taken in the tropical Sontocomapan estuary, southern Gulf of Mexico, in June 2018 and October 2019. A total of 21 zooplankton were recognized, all of them present in the lower estuary. Results showed significant differences (p < 0.05) in the FRic and FDiv values between the two zones, as well in the CWM metric. Results of the FCA showed that the lower estuary was characterized by herbivorous filter feeders that use watery bodies, flattened body forms, mucus houses, or ‘wings’ for buoyancy; highly transparent bodies (associated with gelatinous body structure) for camouflage and predators’ avoidance and, shells or carapaces as antipredator tactics. The upper estuary was characterized by omnivorous cruising predators that use their appendages or swim bladders for buoyancy, with ‘medium’ and ‘low’ levels of transparency, associated with chitinous and skin-protected body structures, which provide alternative ways for camouflage and spines or fast swimming behavior to protect from predators. These findings evidenced that the upper and lower zones of an estuary exhibit differences in the function of the zooplankton community and shed new light on the comprehension of estuaries’ ecological function.